THE IMPACT OF CORPORATE GOVERNANCE ON ROA AND STOCK RETURN - Bagas Wicaksono; Sugeng Wahyudi (Jurnal Akuntansi dan Pajak, 2022)
This paper aims to examine the effect of corporate governance on company performance. This study uses components of corporate governance, namely, independent ownership, concentrated ownership, board independence and board size as independent variables. The dependent variable used to describe the company's performance is return on assets and stock return. This research population is companies listed on IDX and samples taken from companies from the manufacturing sector from 2016 to 2019 collected 540 samples. Based on the results of the research analysis, board independence and board size variables have a significant positive effect on the return on assets variable that supports agency theory and ownership concentration variables have an influence on stock returns that support signal theory